Spatial And Temporal Analysis Of Changes In Mangrove Vegetation Area In Jawai District, Sambas Regency During 2013-2023 - Yunita, Nurul Fatimah; Merdekawati, Dewi; Usman, Muhammad; Agam, Beryaldi; Fikri, Muhammad Zakiyyul; Maryono,; Masara'T, Sudirman (Maritime Park: Journal of Maritime Technology and Society, 2025)
Monitoring mangrove vegetation is an essential initial step in mangrove management. The aim of this study was to observe the spatial and temporal changes in the coverage and extent of mangrove vegetation in the Jawai District. The method used in this research was remote sensing through geometric analysis of changes in coverage and the density of mangrove vegetation using the Normalized Difference Vegetation Index (NDVI) and Green Chlorophyll Index (GCI) as indicators of mangrove vegetation health. The results of the analysis using Landsat 8 satellite imagery recorded in 2013 and 2023 as input data revealed that the extent of mangrove vegetation coverage experienced both increases and decreases in certain villages. A total of six villages saw an increase in mangrove vegetation covering 171.2 hectares, including Dungun Laut, Sentebang, Sei Nyirih, Parit Setia, Pelimpaan, and Sarang Burung Kuala. Meanwhile, five villages experienced a reduction in mangrove vegetation area, comprising Bakau, Sarang Burung Usrat, Sarang Burung Kolam, Sei Nilam, and Sarang Burung Danau. The village with the largest increase in mangrove area was Parit Setia, with an addition of 45.075 ha, while the greatest decrease occurred in Sarang Burung Usrat, with a reduction of 32.917 ha. Furthermore, the NDVI and GCI values showed a similar pattern, with an increase in index values from 2013 to 2023. When the NDVI value increases, the GCI value also increases. The density of mangrove vegetation based on NDVI ranged from 0.0249 to 0.4300 in 2013, and increased in 2023, ranging from 0.0451 to 0.5117. The GCI values in 2013 ranged from 0.0030 to 1.1628, and in 2023 they ranged from 1.0499 to 2.5708.